Friedreich's Ataxia (FRDA) is an extremely rare cause of autosomal recessive ataxia in Chinese Han population - Zeng, Junsheng; Wang, Junling; Zeng, Sheng; He, Miao; Zeng, Xianfeng; Zhou, Yao; Liu, Zhen; Jiang, Hong; Tang, Beisha (Journal of the neurological sciences, 2015)
Friedreich's Ataxia (FRDA) is a very common cause of hereditary autosomal recessive ataxia among western Europeans. We aim to define the frequency of FRDA in Chinese Han population due to the lack of reports of FRDA in China. The GAA trinucleotide repeats in the FXN gene were analyzed by triplet repeat-primed PCR (TP-PCR) in 122 unrelated hereditary ataxia (HA) and 114 unrelated hereditary spastic paraplegia (HSP) patients. The GAA copy numbers in the FXN gene of all the subjects ranged from 5 to 16. There were no FRDA patients that could be diagnosed base on the results of TP-PCR. It suggests that FRDA is a very rare cause of inheritance ataxia and FRDA genetic analysis should not be used as a routine genetic diagnosis test in China.